PENGEMBANGAN E-LKPD BERBASIS WORDWALL WEB PADA MATERI BENTUK INDONESIAKU SISWA KELAS V SDN SENTUL 04 KOTA BLITAR - Essa Dianti, Putri; Tri Oktaviani, Ragil; Nur Amalia, Shofi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research intends to develop a Wordwall Web-based E-LKPD with the material "My Indonesian Form" for class V students at SDN Sentul 04 Blitar City, determine the feasibility of the developed Wordwall Web-based E-LKPD, and determine the effectiveness of using the Wordwall Web-based E-LKPD in learning the material " "My Indonesian Shape" for fifth grade students at SDN Sentul 04, Blitar City. A research and development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model was used in this research. It is hoped that the results of this research will be able to increase students' interest and motivation in learning, facilitate more interactive and enjoyable learning, provide effective alternative learning media, and improve the quality of teaching and learning in schools through the use of technology-based learning media.